Analisis Psikometris: Uji Validitas dan Reliabilitas Alat Ukur Kecemasan terhadap Kekerasan Seksual pada Mahasiswa - Triyantoro, Davit Bagus; Salsabila Aven, Ghina; Yuliasari, Hesty; Erwan Syah, Muhammad (Inquiry: Jurnal Ilmiah Psikologi, 2025)
Almost everyone can potentially become a victim of sexual violence and experience varying levels of anxiety when faced with it. This study aims to develop a tool to measure anxiety about sexual violence in college students. The sample size was 286 students, using a purposive sampling technique. Data were obtained from the Sexual Violence Anxiety Scale, developed based on Nevid's theory and comprising 24 items, covering three aspects: physical, behavioral, and cognitive. The data analysis methodology used to test construct validity was Confirmatory Factor Analysis (CFA), processed using the Jamovi data analysis application. The test items were proven to be unidimensional (valid), and the scale's reliability was coefficient  Cronbach's Alpha of 0.975, indicating consistency in measuring anxiety about sexual violence in the students sampled in this study